2012
DOI: 10.2166/wst.2012.166
|View full text |Cite
|
Sign up to set email alerts
|

Determination and occurrence of organic micropollutants in reverse osmosis treatment for advanced water reuse

Abstract: The growing demand on water resources has increased the interest in wastewater reclamation for multiple end-use applications such as indirect and direct potable reuse. In these applications, the removal of organic micropollutants is of a greater concern than in conventional wastewater treatment. This article presents a collection of data of trace organic micropollutants in an urban wastewater treatment plant (WWTP) in North East Spain using reverse osmosis (RO) membrane treatment. The RO rejection values of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…However, the types of emerging and priority pollutants frequently appeared and at their concentrations in the municipal ROC has only been reported in a few studies. 36,37 Test results indicated that many emerging and priority pollutants that belong to PAHs, PAEs, PPCPs, herbicides, and ame retardants appeared in the ROC. Regarding the PAHs, naphthalene, acenaphthene, uorene, phenanthrene and anthracene were detected at relatively low concentrations of 0.03-0.23 mg L À1 .…”
Section: Source Of the Emerging And Priority Pollutantsmentioning
confidence: 99%
“…However, the types of emerging and priority pollutants frequently appeared and at their concentrations in the municipal ROC has only been reported in a few studies. 36,37 Test results indicated that many emerging and priority pollutants that belong to PAHs, PAEs, PPCPs, herbicides, and ame retardants appeared in the ROC. Regarding the PAHs, naphthalene, acenaphthene, uorene, phenanthrene and anthracene were detected at relatively low concentrations of 0.03-0.23 mg L À1 .…”
Section: Source Of the Emerging And Priority Pollutantsmentioning
confidence: 99%
“…In that line, Sun et al (2012) Authors concluded that ozonation is a feasible polishing process, subsequent to biological treatment, for removal of residual antibiotics from swine wastewater, and the primary reaction mechanism was direct oxidation via ozone rather than indirect oxidation via hydroxyl radicals. Gomez et al (2012) The study by Kosjek et al (2012) processes. Authors found that main micropollutants of concerns were cadmium, di-2-ethylhexyl phthalate (DEHP), diuron, alkylphenols, and chloroform while the emerging substances of particular concern were by-products, organic chemicals (e.g.…”
Section: Alkylphenols (Apsmentioning
confidence: 99%
“…It has been demonstrated that some micropollutants such as atrazine, can be effectively removed by RO and, to a lesser extent, by nanofiltration (NF) membranes (Baier et al, 1987;Duranceau and Taylor, 1992;Ventresque et al, 1997;van der Bruggen et al, 1998;Crozes and Seacord, 2001). More recently, Comerton et al (2007), van der Bruggen et al (2002), Kiso et al (2001), Nghiem, et al (2004, Mulford et al (1999), Kimura et al (2004), Schafer et al (2003), Yangali-Quintanilla et al (2010a, b), Gomez et al (2012), and Ozaki and Li (2002) are among those who have bench tested RO and/or NF effectiveness.…”
Section: Introductionmentioning
confidence: 98%
“…(, b), Gomez et al . (), and Ozaki and Li () are among those who have bench tested RO and/or NF effectiveness.…”
Section: Introductionmentioning
confidence: 99%